The impact of a self-selected time restricted eating intervention on eating patterns, sleep, and late-night eating in individuals with obesity - Simon, Stacey L.; Blankenship, Jennifer; Manoogian, Emily N. C.; Panda, Satchidananda; Mashek, Douglas G.; Chow, Lisa S. (Frontiers in Nutrition, 2022)
Background: Time restricted eating (TRE), limiting eating to a specific daily window, is a novel dietary intervention, but the mechanisms by which TRE results in weight loss remain unclear. The goal of the current study was to examine changes in eating patterns, sleep, and late-night eating, and associations with health outcomes following in a secondary analysis of a 12-weeks of a self-selected TRE intervention. Methods: Twenty participants 18-65 years with BMI ≥25 kg/m2 completed the 12-week trial. Participants randomized to TRE (n=11) were instructed to eat during a self-selected 8-hour window, while the non-TRE group (n=9) followed their typical eating habits. All participants logged oral intake using the myCircadian Clock mobile application throughout the entire intervention. Anthropometrics, HbA1c, an oral glucose tolerance test, and two weeks of actigraphy monitoring were completed at pre-intervention and end-intervention. Independent samples t-tests compared differences between groups. Data are presented as mean ± standard deviation. Results: At preintervention, late night eating was significantly associated with higher fasting glucose (r = 0.59, p = 0.006) and higher HbA1c (r=0.46, p = 0.016). The TRE group significantly delayed the timing of the first eating occasion by 2.72 ± 1.48 hours relative to wake time (p<0.001) and advanced the timing of the last eating occasion by 1.25 ± 0.8 hours relative to bedtime (p<0.001). The non-TRE group, on average, maintained their eating pattern. Sleep measures did not change from pre- to end-intervention, however greater restriction of the eating window was associated with longer sleep duration at end-intervention (β = -0.46 [95% CI –9.2,-0.4], p = 0.03). The TRE group significantly reduced the prevalence of late night eating (eating within 2 hours of bedtime) by 14 ± 6% (p=0.028) with 63% of participants completely eliminating late night eating at end-intervention. Conclusion: A self-selected TRE intervention significantly shifted meal timing, reduced late-night eating while prolonging sleep duration.